DETERMINANTS OF PHYSICAL ACTIVITY IN A COLLEGE STUDENTS’ ASSOCIATION OF SOUTH SUMATERA INDONESIA (Proceedings of the International Conference on Public Health, 2017)
Although physical activity has significant benefits for health, a lot of Indonesian people were not sufficiently active. Indonesian Ministry of Health reported South Sumatera as one of province which has a lot of insufficiently active people (26,7%). It was higher than the average number of insufficiently active people in Indonesia. Thus, examining the determinants is an important prerequisite for designing effective programs. This study investigated predisposing (knowledge and attitudes), enabling (time and facilities availability), and reinforcing (family, friends, and health professional support) factors determined physical activity for the college students in South Sumatera. This study used cross-sectional design. Data were analyzed for 50 members of the college students’ association who completed a questionnaire. Result showed 60% of respondents were sufficiently active. Chi square test revealed that knowledge (p=0,003; OR=8,0), attitudes (p=0,001; OR=21,0), and facilities (p=0,012; OR=6,5) had meaningful relationship with physical activity. There was no relationship between time availability (p= 0,636), family (p= 0,302), friends (p=1,0), and health professional support (p= 0,861) with physical activity. The findings clarified the factors that determined physical activity in the college students’ association were knowledge, attitudes, and facilities. These factors may help in the formulation of intervention strategies to make people more physically active.
Keywords: determinants; physical activity; college students